Pengaruh Sanksi Pajak, Sosialisasi, Sistem Pajak, Tax Avoidance Terhadap Hambatan Pemungutan Pajak Pada Wajib Pajak Orang Pribadi Yang Melakukan Pekerjaan Bebas Di Kabupaten Jember - Salma Watun; Suwignyo Widagdo; Nanda Widaninggar (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2020)
This study aims to analyze the effect of tax sanctions, tax socialization, tax system, and tax avoidance on the barriers to the tax collection. This research method was quantitative. The population in this study are all individual taxpayers who do free work in Jember Regency. By accidental sampling, the samples are fifty respondents of Individual Taxpayers who do free work. Data collection using a questionnaire, and the data analysis method uses multiple linear regression analysis. The results showed that tax sanctions, tax system, tax avoidance had a significant effect on the obstacles to tax collection, while tax socialization has no significant effect on barriers to tax collection. Since the tax socialization had no impact, fiscus should use the strategy to avoid the barriers of tax collection by using account representative assistance in active counseling to the taxpayer.